2012
DOI: 10.1002/ajmg.a.35554
|View full text |Cite
|
Sign up to set email alerts
|

“I want to know what's in Pandora's box”: Comparing stakeholder perspectives on incidental findings in clinical whole genomic sequencing

Abstract: Whole genomic sequencing (WGS) promises significant personalized health benefits, and its increasingly low cost makes wide clinical use inevitable. However, a core challenge is "incidental findings" (IF). Using focus groups, we explored attitudes about the disclosure of IF in clinical settings from three perspectives: Genetics health-care professionals, the general public, and parents whose children have experienced genetic testing. Analysis was based on a framework approach. All three groups considered practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
193
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(208 citation statements)
references
References 39 publications
13
193
1
1
Order By: Relevance
“…Most professionals considered recontacting to be desirable and the shared responsibility of professionals and patients. Only Townsend et al 49 reported on the duty to recontact in light of WGS; patients' and professionals' opinions were in accordance with the other empirical articles.…”
Section: Empirical Evidence On the Duty To Recontactsupporting
confidence: 54%
See 2 more Smart Citations
“…Most professionals considered recontacting to be desirable and the shared responsibility of professionals and patients. Only Townsend et al 49 reported on the duty to recontact in light of WGS; patients' and professionals' opinions were in accordance with the other empirical articles.…”
Section: Empirical Evidence On the Duty To Recontactsupporting
confidence: 54%
“…20 The more recent literature relatively more often raised ethical arguments against a duty to recontact, thereby emphasizing respect for patient autonomy, which is thought to become even more important in light of WGS. 49,54 Hunter et al 15 stated that there is a greater justification for recontacting former patients with definite, significant information about a life-threatening disease than for a small increased risk for a slowly progressive disease. They also noted that information may affect people differently, and therefore recontacting might be beneficial for some, whereas it might be harmful to others.…”
Section: Elsi Issues Regarding the Duty To Recontactmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in our focus group study, which explored lay and patient attitudes about WGS IF clinical disclosure, strongly supported the right to say no to disclosure. 5 Following Andorno 3 we maintain that the right not to know must be offered but cannot be presumed, and must be 'activated' by a person's explicit choice. Also, it is not an absolute right; it may be restricted when disclosure relates to serious harm to third persons (p 435).…”
mentioning
confidence: 99%
“…[12][13][14][15][16] Options suggested range from full disclosure of all results to disclosing only those with known clinical significance, and/or which have an intervention that can prevent, treat, or mitigate disease. What our examples highlight is that it may be extremely difficult to withhold details of IFs, even if a conclusion is that they are not clinically significant, because further investigations of the patient, and their relatives, may be required to come to this conclusion.…”
Section: Disclosure Of Resultsmentioning
confidence: 99%